2007
DOI: 10.1017/s0950268806007734
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of bacterial meningitis in Asia using enhanced CSF testing: polymerase chain reaction, latex agglutination and culture

Abstract: To enhance the detection of bacterial meningitis in an East Asian surveillance study, we employed cerebrospinal fluid (CSF) bacterial culture, latex agglutination (LA) and polymerase chain reaction-enzyme immunoassay (PCR-EIA) testing for Haemophilus influenzae type b (Hib) and Streptococcus pneumoniae (Sp). The sensitivity and specificity of CSF PCR-EIA testing was compared to LA and culture. A meningitis case was defined by one positive result for any of the three tests. The sensitivity of H. influenzae CSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 15 publications
4
49
0
2
Order By: Relevance
“…This additional PCR testing increased overall detection of laboratory-confirmed Hib disease, compared with detection by culture alone. The diagnostic yield by PCR of CSF specimens in this study is consistent with the findings of Kennedy et al [17], who found that PCR to test for Hib and pneumococci in CSF identified additional children who did not receive a diagnosis by either culture or antigen testing.…”
Section: Discussionsupporting
confidence: 91%
“…This additional PCR testing increased overall detection of laboratory-confirmed Hib disease, compared with detection by culture alone. The diagnostic yield by PCR of CSF specimens in this study is consistent with the findings of Kennedy et al [17], who found that PCR to test for Hib and pneumococci in CSF identified additional children who did not receive a diagnosis by either culture or antigen testing.…”
Section: Discussionsupporting
confidence: 91%
“…This research was undertaken because prospective, population-based studies of Hib meningitis had not been previously done in Asian populations and because of a strong suspicion that Hib meningitis was being underdiagnosed in Asian children, leading to a false impression that this disease was not an important public health problem. To the investigators' surprise, the incidence rates found in the IVI study ( table 3 ) were indeed low in each of the 3 sites [41][42][43] .…”
Section: Letting the Chips Fall Where They Maymentioning
confidence: 81%
“…For these reasons using this case definition, the number of clinical cases, may be significantly underestimated [6]. Various authors have suggested alternative diagnostic and epidemiological means, to overcome this problem, including antigen detection methods [69,70] as well as vaccine-probe study designs [71]. Laboratory parameters focusing on both quantitative and qualitative antibody characteristics have been suggested as markers of protection against disease [72][73][74][75][76].…”
Section: Vaccine Efficacy and Effectivenessmentioning
confidence: 99%